1990
DOI: 10.1177/002248719004100206
|View full text |Cite
|
Sign up to set email alerts
|

Differences Between Graduates of 4-Year and 5-Year Teacher Preparation Programs

Abstract: A 10-year comparison of graduates from 4-and 5-year teacher education programs at the same institution revealed significant differences between graduates of the two programs. Significantly more 5-year graduates entered and stayed in teaching than graduates of the 4-year program. Graduates of the 5-year program were more satisfied with their career and perceived the quality of their program to be higher than the 4-year graduates did. Limitations of the study and alternative explanations for these differences ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(37 citation statements)
references
References 16 publications
0
35
0
2
Order By: Relevance
“…The challenge in preparing pre-service teachers to teach reading is that they must be able to link new knowledge learnt through coursework to instructional practices through the practicum or internships. Reading teacher preparation that is field based and that emphasises practicum experiences seems to have the most positive effects, specifically supervised, (Andrew 1990). Expertise to teach reading matters more than curriculum materials, pedagogical approaches and reading programmes (Allington 2002), and it can be developed through experiences, careful deliberation and reflection on practice, usually through supervision by knowledgeable mentors (Cochran-Smith 2000) using evidence-based reading research practices.…”
Section: Integrationmentioning
confidence: 99%
“…The challenge in preparing pre-service teachers to teach reading is that they must be able to link new knowledge learnt through coursework to instructional practices through the practicum or internships. Reading teacher preparation that is field based and that emphasises practicum experiences seems to have the most positive effects, specifically supervised, (Andrew 1990). Expertise to teach reading matters more than curriculum materials, pedagogical approaches and reading programmes (Allington 2002), and it can be developed through experiences, careful deliberation and reflection on practice, usually through supervision by knowledgeable mentors (Cochran-Smith 2000) using evidence-based reading research practices.…”
Section: Integrationmentioning
confidence: 99%
“…Surveys are sometimes used to gather information about teachers' entry into the profession (Andrew, 1990;Andrew & Schwab, 1995;, their perceptions of teaching as a profession (Lutz & Hutton, 1989), and their intention to remain in the profession . Other surveys collect background information on teachers to use as representations of teacher quality characteristics (i.e., number of graduate and undergraduate courses taken, undergraduate institution, certification status, and major; Andrew, 1990;Andrew & Schwab, 1995).…”
Section: What Instruments Are Used To Measure Teacher Quality?mentioning
confidence: 99%
“…A number of recent studies have found that graduates of extended programs are not only more satisfied with their preparation; they are viewed by their colleagues, principals, and cooperating teachers as better prepared; are as effective with students as much more experienced teachers; and are much more likely to enter and stay in teaching than their peers prepared in traditional undergraduate programs (Andrew, 1990;Andrew & Schwab, 1995;Arch, 1989;Denton & Peters, 1988;Dyal, 1993;Shin, 1994).…”
Section: Teacher Education In the United States: The Luck Of The Drawmentioning
confidence: 99%